2009
DOI: 10.1038/nm.2049
|View full text |Cite
|
Sign up to set email alerts
|

Foxo1 integrates insulin signaling with mitochondrial function in the liver

Abstract: Type 2 diabetes is a complex disease that is marked by the dysfunction of glucose and lipid metabolism. Hepatic insulin resistance is especially pathogenic in type 2 diabetes, as it dysregulates fasting and postprandial glucose tolerance and promotes systemic dyslipidemia and nonalcoholic fatty liver disease1,2. Mitochondrial dysfunction is closely associated with insulin resistance and might contribute to the progression of diabetes3,4. Here we used previously generated mice5 with hepatic insulin resistance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
332
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(360 citation statements)
references
References 33 publications
26
332
1
1
Order By: Relevance
“…Thus, the ability of 6KR to tune down expression of solute carriers might be part of a protective function. Interestingly, the mitochondrial gene expression signature of FoxO1 in ␤-cells appears to differ substantially from that in liver (39). Whether this depends on different levels of deacetylation in the two organs is an interesting question that will have to be addressed in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ability of 6KR to tune down expression of solute carriers might be part of a protective function. Interestingly, the mitochondrial gene expression signature of FoxO1 in ␤-cells appears to differ substantially from that in liver (39). Whether this depends on different levels of deacetylation in the two organs is an interesting question that will have to be addressed in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the relationship with PGC1A, the present study found no relationship between GIR and downstream factors, including PGC1α protein production, nuclear respiratory factor-1 (NRF1), mitochondrial transcription factor A (TFAM) or mitochondrial genes and proteins. Post-transcriptional regulation of PGC1α, such as acetylation [47], may in part account for the dissociation between gene expression and protein abundance and the expected downstream effects.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 As FoxO1 was implicated in mitochondrial regulation, 12,20 we asked if AS1842856 interferes with mitochondrial function in adipocytes. Western blot analysis of mitochondrial proteins revealed 2.6-fold (P < 0.01) upregulation of respiration chain complex I (C1) and 3.9-fold (P < 0 .01) elevation of complex III (C3) in matured adipocytes when compared with pre-adipocytes ( Fig.…”
Section: As1842856 Reduced Mitochondrial Protein Levelsmentioning
confidence: 99%
“…Oil Red O retained in the cells was extracted with isopropanol, and quantified by the absorbance (O. D.) at 510 nm. 28 Western blot For cell lysates, the cells were washed with ice-cold PBS (Caisson Labs) and lysed with a Bullet Blender Ò (Next Advance, Inc..), in PLC lysis buffer: 20,29 (30 mM Hepes, pH 7.5, 150 mM NaCl, 10% glycerol, 1% Triton X-100, 1.5 mM MgCl2, 1 mM EGTA, 10 mM NaPPi, 100 mM NaF, 1 mM Na3VO4) supplemented with protease inhibitor cocktail (Roche), 1 mM PMSF, 10 mM TSA (Trichostatin A, Selleckchem) and 5 mM Nicotinamide (Alfa Aesar). Total protein concentrations of the cell lysates were determined using the DC protein assay (Bio-Rad).…”
Section: Oil Red O Stainingmentioning
confidence: 99%
See 1 more Smart Citation